PEMBERDAYAAN PEREMPUAN DALAM PENINGKATAN EKONOMI KELUARGA MELALUI PRODUKSI KRUPUK BERBAHAN TEPUNG DESA KALIPENGGUNG KEC. RANDUAGUNG LUMAJANG - Imaniar Mahmuda; Ahmadi; Hafid; Ismatul Rofi’a; Lailatul Maulida ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2024)
Family economic empowerment, especially in rural areas, is key in reducing poverty. One effective approach is to involve women in developing micro-enterprises, such as cracker production. Through this business, women not only increase family income, but also gain economic independence. Making flour crackers is one of the empowerment businesses operating in the food sector in Kalipenggung village, Kec. Randuagung Lumajang. This article describes the empowerment of women in improving the family economy through the production of crackers made from flour in Kalipenggung Village, Kec. Randuagung Lumajang. This community service activity is carried out using the participatory rural approach (PRA) method, which is a method of educating the community through counseling, demonstrations and mentoring. The result of this research is that the process of empowering housewives in processing flour crackers consists of three stages, namely the awareness stage which is carried out through motivation, the ability transformation stage which is carried out through initial conditioning with the preparation of facilities and infrastructure in processing flour crackers. Then the implementation process is the core of the empowerment program in the activity of processing flour crackers which is carried out with direct practice and the stage of increasing intellectual abilities which is carried out with direct assistance and independence by giving mothers the freedom to do it independently.